Phylogeny and morphology of the freshwater red alga Nemalionopsis shawii (Rhodophyta, Thoreales) from Nepal - Necchi, Orlando [UNESP]; West, John A.; Rai, Shiva K.; Ganesan, E. K.; Rossignolo, Natalia L. [UNESP]; Goer, Susan L. de (Wiley-Blackwell, 2016)
Phylogenetic relationships and morphological characters are presented for a population of Nemalionopsis shawii Skuja collected from Nepal. Molecular data (sequences of rbcL and cox1) were generated and morphological characters were described in detail. The rbcL sequence analyses showed that specimens from Nepal are most similar to N.shawii from Indonesia and Japan and that these entities form a clade with high support (>95% bootstrap and 0.95 posterior probability). The cox1 barcode sequence, however, only had 90.9-91.9% identity with specimens of N.shawii from Hawaii. The rbcL sequence of the specimen from Nepal was positioned in a clade having sequence identity of 99.3-99.7% with three samples: N.shawii from Indonesia and two from Japan identified as N.tortuosa. The comparison of morphological characters of Nemalionopsis from Nepal allowed unequivocal identification with N.shawii. Identifications from previous studies using molecular data were mistaken since most reports of N.shawii are actually of N.tortuosa or vice-versa. This confusion of names presumably occurred because most specimens previously sequenced were from culture collections or from Chantransia' stages. Small tufts of Chantransia' stage were observed growing epiphytically on gametophytes and on the basal system. Carpogonia and spermatangia were fully described in specimens from Nepal. Monosporangia were not observed, whereas carposporangia were unequivocally described for the first time in the genus. An unusual flat strap-like basal system was observed, interpreted as an additional mode of maintenance in nature under unfavorable environmental conditions.
Keywords: Chantransia' stage; basal system; carposporangia; cox1; molecular phylogeny; rbcL; sexual reproduction